Accentuating CircRNA-miRNA-Transcription Factors Axis: A Conundrum in Cancer Research - Singh, Deepti; Kesharwani, Prashant; Alhakamy, Nabil A.; Siddique, Hifzur R. (Frontiers in Pharmacology, 2022)
Circular RNAs (circRNAs) are the newly uncovered class of non-coding RNAs being cognized as profound regulators of gene expression in developmental and disease biology. These are the covalently closed RNAs synthesized when the pre-mRNA transcripts undergo a back-splicing event. In recent years, circRNAs are gaining special attention in the scientific world and are no longer considered as “splicing noise” but rather structurally stable molecules having multiple biological functions including acting as miRNA sponges, protein decoys/scaffolds, and regulators of transcription and translation. Further, emerging evidence suggests that circRNAs are also differentially expressed in multiple cancers where they play oncogenic roles. In addition, circRNAs in association with miRNAs change the expression patterns of multiple transcription factors (TFs), which play important roles in cancer. Thus, the circRNA-miRNA-TFs axis is implicated in the progression or suppression of various cancer types and plays a role in cell proliferation, invasion, and metastasis. In this review article, we provide an outline of the biogenesis, localization, and functions of circRNAs specifically in cancer. Also, we highlight the regulatory function of the circRNA-miRNA-TFs axis in the progression or suppression of cancer and the targeting of this axis as a potential therapeutic approach for cancer management. We anticipate that our review will contribute to expanding the knowledge of the research community about this recent and rapidly growing field of circRNAs for further thorough investigation which will surely help in the management of deadly disease cancer.